Replication for: Single torradovirus infections explain the mysterious cassava frogskin disease in the Americas - Cuellar, Wilmer Jose; Jimenez Polo, Jenyfer; Pardo Garcia, Juan Manuel; Gil Ordoñez, Alejandra; Caicedo Hidalgo, Sara Maria; Alvarez Quinto, Robert Alexander; Dimitre, Mollov (2025)
Sentinel cassava plants were exposed to high disease pressure in the field to promote root symptom expression. After visual inspection, symptomatic plants were propagated in a screenhouse for a second growth cycle. Molecular analyses, including RT-PCR and HTS, were conducted to identify associated pathogens and investigate their link to cassava frogskin symptoms.